Essays on transportation cost, social security retirement income and housing market - HUANG, Naqun (Institutional Knowledge at Singapore Management University, 2017)
This dissertation comprises three papers that study how transportation cost affect price distribution across a city, how home equity affects the timing of pension withdrawal, and potential implications of macroprudential policies on the price informativeness. Specifically, the first paper examines how a change in the cost of car ownership affects housing price gradient with respect to distance from the central business district (CBD) in Singapore. The second paper investigates how household home equity affect the timing of claiming Social Security Retirement Income (SSRI) in the United States. The third paper explores how countercyclical policies in Singapore real estate market affect price informativeness. Chapter 2 studies one important factor that helps to explain the price distribution of housing throughout a city. It is the acquisition cost of transportation. One key finding is obtained. When the cost of owning a car increases, the price of housing closer to the city center increases relative to housing farther away from the CBD, suggesting that increases in the price of a car cause individuals to increase their willingness to pay to locate closer to the CBD. This is consistent with the predictions from the monocentric city model that allows for two modes of transportation. Chapter 3 examines the question that help to explain the timing when elderly individuals decide to receive SSRI benefits. The question investigates the trade-off between Social Security Retirement Income (SSRI) and home equity, two largest components among the various sources of financial assets of the elderly. Three key findings are obtained. An increase in the value of a home causes elderly individuals to delay SSRI claiming once they are eligible during the housing boom period, but we do not find a statistically significant impact on the claim decision during the bust period. Second, higher housing values have a positive effect on the likelihood of retirement in both the boom and bust period. Third, pension eligibility plays a role on the impact of home equity on retirement. ii Chapter 4 address one question that helps us to understand the consequences of macroprudential policies. It asks how the countercyclical policies that are designed to deter speculators by increasing transaction cost affect price informativenss in real estate market. Two key findings are obtained. First, speculative trade decreases after dramatic increase in the transaction cost. Second, price trend along sales sequence shows significant increasing pattern. It suggests that price might not accurately reflect the true value of houses without market players who play a role in promoting informational efficiency.